(untitled) (Journal of Applied Learning and Teaching, 2024)
Research on university professors’ digital competence is essential because the university professor is the most valuable human resource educational institutions have and is responsible for carrying out various actions to achieve institutional purposes. The present study aimed to analyze university professors’ self-perception of digital competence. It is a quantitative, non-experimental, descriptive, and cross-sectional study. The sample was 122 professors from one private university in Peru. Also, a significant relationship was found between gender and knowledge of methodological strategies for networking. The teacher’s age was the most relevant factor in digital competence, affecting teachers’ ability to know and use communication and information tools. A significant percentage of teachers did not participate in training activities and did not evaluate their teaching practices with ICT; likewise, there was low participation in projects and groups to innovate and research teaching topics with ICT. Based on the deficiencies found, a continuous training program is expected to be designed to raise teachers’ digital competence levels.